AB Initio Study of Coinage Metal Doped Graphene Nano Ribbons (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
The electronic and transport properties of both zigzag graphene nanoribbons (ZGNRs) and armchair graphene nanoribbons (AGNRs) doped with coinage metals (CM) Cu, Au and Ag has been investigated by employing ab-initio approach using non equilibrium Green's function combined with density functional theory. In Cu-doped ZGNRs, it is observed that the linear positive bias I–V curve and conductance is higher due to doping towards the centre of the ribbon. Doping at strategic positions yield currents such that the semiconductor to metal transition takes place in all the Cu-doped AGNRs. Au-doped ZGNRs exhibit stable structure and semimetallic nature is predicted with a high DOS peak distributed over a narrow energy region at the Fermi level. Our calculations for the magnetic properties predict that Au functionalization leads to semiconducting nature with different band gaps for spin up and spin down. Au-doped AGNRs are semiconducting with lower total energy for the FM configuration, and the I-V characteristics reveal semiconductor to metal transition. The spin injection is voltage controlled in all the investigated Au-doped AGNRs. The transmission spectrum (T.S) of Ag-doped ZGNRs present heightened electronic activity due to interaction between Ag impurities and edge states of the ZGNRs. Significant transport properties applicable for various device applications at the nano-regime are thus reported in all the coinage metal doped GNRs.
Keywords: Graphene; Zigzag; Armchair; Copper; Gold; Silver; Electronic; Transport; Spin